Inverse correlation of kidney interstitial cells expansion with hemoglobin level and erythropoietin expression in single and repeated kidney ischemic/reperfusion injury in mice - Dian Prasetyo Wibisono; Nur Arfian; Muhammad Mansyur Romi; Wiwit Ananda Wahyu Setyaningsih; Dwi Cahyani Ratna Sari (Universitas Gadjah Mada, 2019)
Ischemic/reperfusion injury (IRI) causes acute kidney injury that may lead to chronic kidney disease. We investigated the correlation between kidney interstitial cells expansion, hemoglobin level, and erythropoietin expression as the chronic effects of single and repeated kidney IRI in mice. We created an IRI model using male Swiss mice by clamping the bilateral renal pedicles. Subjects were divided into four groups that contained six mice each: control/sham operation, single acute IRI, single chronic IRI, and repeated IRI. Our results showed that the single chronic and repeated IRI groups significantly increased the tubular injury score, decreased the hemoglobin level, and increased erythropoietin expression compared with the control. Lower hemoglobin levels in all of the groups compared with the control was associated with erythropoietin resistance. In single chronic and repeated kidney IRI, there were decreased creatinine levels compared with the control. The decreased creatinine levels from the single acute IRI group to the single chronic IRI group, suggesting a repair phase of IRI starting on day 7 occurred in the single chronic IRI group. A macrophage marker, CD68, and an inflammatory mediator marker, MCP-1, significantly increased in all IR groups, indicating inflammation occurred due to IRI. In conclusion, chronic and repeated kidney IRI induced interstitial cells expansion and inflammation associated with anemia.